Cateterismo cardíaco, diagnóstico (angiografia) e terapêutico (angioplastia) na doença arterial coronária dos pacientes diabéticos - Lima, Valter C. [UNIFESP] (2007)
Screening, diagnosis and revascularization of coronary artery disease (CAD) in type 2 diabetes mellitus are major challenges for current clinical practice. Diagnostic (angiography) and therapeutic (angioplasty) cardiac catheterization are important resources for the clinical assessment and management of coronary atherosclerosis. Anatomic peculiarities of CAD in diabetics can be well characterized by angiography, associated or not by intravascular ultrasound. The worse outcome following coronary revascularization procedures, either angioplasty or surgery, in diabetic is one of the main fields of clinical research. In spite of controversies, about one quarter of angioplasty and one third of surgical revascularization procedures are performed in diabetics. Two ongoing, large, randomized, multicentric trials are investigating the best management of CAD in diabetics. The BARI 2D trial is randomizing asymptomatic or mildly symptomatic patients with CAD for either medical therapy or revascularization (angioplasty or surgery, according to the best clinical judgment). The FREEDOM trial is randomizing stable patients with multivessel CAD for either angioplasty with drug eluting stents or surgery, with or without extracorporeal circulation. While the evidences are not available, in order to decide on the best revascularization procedure for individual patients, medical practice has been balanced according to a number of variables. Conditions that favor angioplasty: short lesions, lesions in large vessels, absence of left anterior descending artery disease, previous coronary bypass surgery and high surgical risk due to co-morbidities. Conditions that favor surgery: long lesions, lesions in small vessels, presence of left anterior descending artery disease and need for associated valve surgery.